Modeling the Influence of Meteorological Variables on Runoff in a Tropical Watershed - Ekwueme, Benjamin Nnamdi; Agunwamba, Jonah C. (Salehan Institute of Higher Education, 2020)
Proper understanding of the historical annual runoff characteristics with respect to climate impacts is essential for effective planning as well as the management of water resources in river basins. In this study, the climate-flood model which connects the runoff and climate was developed for Adada River Nigeria. Thirty years records of climatic and runoff data were used to develop a multiple linear regression model. The coefficient of determination was evaluated for the developed model, and the hypothesis was equally tested with the aid of t-test and one-way analysis of variance. The multiple regression analysis indicated that the climate-flood model was statistically signiï¬cant (pË‚0.05) in predicting the annual runoff. The results also show that the climatic variables accounted for 66.1% of runoff variation due to the undisturbed gauging basin of the river. The wind speed and the duration of sunlight were not statistically signiï¬cant predictors of runoff in the area. These results, obtained signify that climate has a major impact on runoff and it could help in understanding the availability of water within the catchment area.Â Doi: 10.28991/cej-2020-03091621 Full Text: PDF